IIUM TRACER STUDY 2014 - Rokis, Rohaiza; Wok, Saodah; Zubairi, Ainol Madziah; Dzulkifli, Mariam Adawiah; Md Ghalib, Mohd. Feham; Abdul Rahman, Shukran; Saidin, Aznan Zuhid; Zul Kepli, Mohd Yazid; Tunku Mokhtar, Tunku Mohar; Wan Husain, Wan Rohaida (Alumni and Career Service Division, 2015)
Much research has been conducted to studying graduates' employability and their pattern of employment after graduation. Research of such nature is knows as Tracer Study. The aim of the tracer study is to track graduates' performance or progress after completing their undergraduate studies. This study on IIUM graduates identifies the employability of graduates from the International Islamic University Malaysia who completed their studies in 2014. A total of 4277 graduates completed the questionnaire of IIUM Tracer Study 2014 assessing various issues related to employment and employability.